Conservation acoustics: Animal sounds, audible natures, cheap nature. Issue 124 (August 2021) - Ritts, Max; Bakker, Karen
Abstract: This paper asks why growing numbers of government agencies, professional conservation authorities, university researchers, citizen scientists, and private companies are turning to bioacoustical approaches for conservation research and management needs. These varied activities describe a set of agendas we examine here under the rubric of "conservation acoustics." More than a scientific response to urgent environmental problems, "conservation acoustics" is a contemporary formation of power-knowledge: digital technologies and associated techno-social innovations that are enhancing capitalism's capacity to appropriate new, previously uncommodified sources of "work/energy" (Moore 2015). By pairing Moore with recent work on the political economy of digital music, we can better grasp the structural forces that have given rise to "conservation acoustics" – including advances in digital sound compression, the economic interests of Big Tech and the territorial ambitions of the environmental state. Within this examination, Donna Haraway reminds us of the importance of listening to the stories scientists tell about themselves, which can reveal epistemological closures and political openings that may not be visible from the grand historical view. At the same time, capitalism's organization of nature via the intermediation of digital sound suggests that Haraway's own insights regarding vision and the "God Trick" require a reframing with respect to sound. We draw from literature reviews, a meta-review of over 2000 scholarly papers on bioacoustics and eco-acoustics, and 15 expert interviews to advance our claims.